2021
DOI: 10.1177/10742484211015535
|View full text |Cite
|
Sign up to set email alerts
|

GCN2 Regulates ATF3-p38 MAPK Signaling Transduction in Pulmonary Veno-Occlusive Disease

Abstract: Pulmonary veno-occlusive disease (PVOD) is a fatal disease of pulmonary vascular lesions leading to right heart failure. Heritable PVOD (hPVOD) is related to biallelic mutation of EIF2AK4 (encoding GCN2), but its molecular mechanism remains unclear. In this study, we aimed to investigate the pathogenesis of PVOD and to find potential drug targets for PVOD. GCN2 dysfunction led to an enhanced transcription of collagen I gene ( col1a1 and col1a2) through decreasing ATF3-dependent p38 phosphorylation inhibition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The TGFβ-induced downstream pathways vary with a consensus on the involvement of p42/p44 Mitogen-Activated Protein Kinase (MAPK). Increased phosphorylation of p38 was associated with increased COL1A1 mRNA levels, in in vitro systems related to pulmonary veno-occlusive disease [ 58 ] and liver fibrosis [ 59 ]. The downstream interactors of p38 affecting COL1A1 mRNA expression were, however, not described [ 58 , 59 ].…”
Section: Literature Search and Resultsmentioning
confidence: 99%
“…The TGFβ-induced downstream pathways vary with a consensus on the involvement of p42/p44 Mitogen-Activated Protein Kinase (MAPK). Increased phosphorylation of p38 was associated with increased COL1A1 mRNA levels, in in vitro systems related to pulmonary veno-occlusive disease [ 58 ] and liver fibrosis [ 59 ]. The downstream interactors of p38 affecting COL1A1 mRNA expression were, however, not described [ 58 , 59 ].…”
Section: Literature Search and Resultsmentioning
confidence: 99%
“…Several studies demonstrated that EIF2AK4 was associated with vascular remodeling ( Lu et al, 2014 ; Nossent et al, 2018 ; Chen et al, 2021 ). One possible mechanism was that EIF2AK4 dysfunction enhanced collagen I gene transcription via the ATF3/p38 pathway, which led to increased collagen deposition in the pulmonary artery ( Chen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that EIF2AK4 was associated with vascular remodeling ( Lu et al, 2014 ; Nossent et al, 2018 ; Chen et al, 2021 ). One possible mechanism was that EIF2AK4 dysfunction enhanced collagen I gene transcription via the ATF3/p38 pathway, which led to increased collagen deposition in the pulmonary artery ( Chen et al, 2021 ). As vascular remodeling is critical for CAL formation of KD, we also investigated the association between EIF2AK4 /rs4594236 polymorphism and CAL or CAA formation of KD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the mutation of GCN2 is linked to the development of PVOD and the expression of GCN2 is significantly decreased in patients with PVOD and MMC-induced rat pulmonary microvascular endothelial cells ( 20 22 ). In addition, Chen et al ( 23 ) found that GCN2 deficiency decreased ATF3-dependent p38 phosphorylation inhibition in development of PVOD. This implies that GCN2 plays an important role in the pathogenesis of PVOD.…”
Section: Discussionmentioning
confidence: 99%